Sposoby ustalenia wysokości odszkodowania w przypadku naruszenia praw autorskich w ramach działalności portalu internetowego w praktyce sądowej na tle wyroku SA w Warszawie z dn. 29 sierpnia 2017 r. w sprawie o sygn. akt VI ACa 600/16 - Skibicki, Rafał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Never before has the infringement of copyrights been such an easy task. The main reason behind that is the Internet and the illegal sharing of the works which goes together with it. It is often said that law can not keep up with the technic. The same happens in this case. What is more, it seems that latest judgments have even weakened the protection of copyrights. In my paper I describe claims available for the authors, with a particular consideration of the claim for compensation for damages on general terms, especially in the light of the precedent judgment of the Court of Appeal in Warsaw from August 29, 2017 (case reference number: VI ACa 600/16)
Keywords: copyright; internet; compensation; copyright infringement; illegal distribution